Transfusi Masif dan Tatalaksana Intensif Post Histerektomi pada Plasenta Akreta - Trsitiarti, Alfi Marita; Yuliantara, Eric Edwin (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Placenta accrete remains a problem in developing countries. The incidence rate has increased over the last 30 years accompanied by the risk of maternal death. Bleeding is still the main cause of death. This rising incidence rate has increased Sectio Caesaria (SC) operations, resulting in greater treatment costs. This is due to its cost management as it requires intensive care and massive use of blood transfusions. This study aims to describe the characteristics, management, and maternal outcomes of placenta accrete spectrum cases. Methods A Cross-sectional study was conducted at Moewardi Hospital Surakarta between January 2016 and December 2021. Sample selection was based on medical records with a suspected diagnosis of PAS. A total of 121 cases of placenta accrete spectrum had been confirmed by anatomical pathology results were analyzed Assessments were carried out on maternal characteristics, risk factors, MAP score, intraoperative management, and postoperative care. Statistical analysis was carried out with a 95% confidence interval (CI), chi-square test, and odds ratio assessment using SPSS edition 23. Results Hysterectomy has more morbidity and maternal complications than conservative management in blood loss, massive transfusion, iatrogenic incident, and a long stay in the Intensive care unit. Conclusions The high rate of morbidity in the management of the placenta accrete spectrum requires comprehensive management to reduce maternal mortality.